Design of Roadways Using Open Road Software: A Comparative Analysis of Conventional and Open Road Software for Highway Design (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Open road software is the latest technology used for designing of roadways. This paper is an analytical comparison of conventional method of highway design and design of highway using open road software. This paper studies the methodology of designing of roadways by comparison with conventional method .Role of software is to provide an accurate means for designing of roadways with predictable and current standards of roadways design and geometric design of highways in 2D and 3D nature.